Midterm review of national health plans: an example from the United Republic of Tanzania - Leonard EG Mboera; Yahya Ipuge; Claud J Kumalija; Josbert Rubona; Sriyant Perera; Honorati Masanja; Ties Boerma (The World Health Organization, 2015)
In the health sector, planning and resource allocation at country level are mainly guided by national plans. For each such plan, a midterm review of progress is important for policy-makers since the review can inform the second half of the plan's implementation and provide a situation analysis on which the subsequent plan can be based. The review should include a comprehensive analysis using recent data - from surveys, facility and administrative databases - and global health estimates. Any midterm analysis of progress is best conducted by a team comprising representatives of government agencies, independent national institutions and global health organizations. Here we present an example of such a review, done in 2013 in the United Republic of Tanzania. Compared to similar countries, the results of this midterm review showed good progress in all health indicators except skilled birth attendance.